Systematic Review: Relationship between Hospital Marketing Mix and Patient Visits and Hospital Selection - Lesmana Putra, Pandu; Gani, Ascobat (Riviera Publishing, 2024)
This study aims to determine the relationship between hospital marketing mix, patient visits, and hospital selection. The study method uses the PRISMA method. Inclusion criteria were journals published from 2018 to 2022, focusing on marketing mix and hospitals. Journal searches were carried out using the keywords